A cellular automata model for monitoring and simulating urban land use/cover changes toward sustainability - Khatibi, Ali; Pourebrahim, Sharareh; Danehkar, Afshin (Journal of Environmental Engineering and Landscape Management, 2018)
This study presents an integrated model based on cellular automata for assessing and simulating land use/cover changes and their impact on the environment. Satellite images from Landsat TM and ETM + sensors from the time period of 1985 to 2014 were applied. Seven static and five dynamic variables were applied. These included elevation, slope, aspect, soil salinity, soil texture, distance from rivers, and roads, and distance from the five classes of land use. The model was validated by a fuzzy reciprocal similarity method. The results showed that this model is suitable for simulating changes in periods of less than 15 years and patches with areas greater than 25 hectares. The model was run for 15 years, beginning with the year 2014. The results for the study area predict that settlement areas will expand; agricultural land, rangeland and barren areas will decline; and forests will remain unchanged until 2029.